PENYIMPANGAN NILAI-NILAI PANCASILA DALAM PRAKTIK KEPEMIMPINAN DI ERA POLITIK MODERN - Meika, Tisnowati Wulan Agustin; Ellen Harum Ismawati; Sofy Hidayatu Mutiya; Rahma Evelyna Hardina Putri; Hilma Amilia Zahiroh; Kusnul Khotimah (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This research examines how the values of Pancasila have been deviated in leadership practices in the modern political era. The objective of this study is to identify the factors leading to these deviations and their impact on leadership structures in Indonesia. The results indicate a decline in the application of Pancasila values, particularly concerning justice and solidarity, due to the influence of globalization and pragmatic politics. The conclusion suggests the need for revitalizing Pancasila values in education and policy to reinforce national identity and a sustainable democratic system.